Atividade antimicrobiana de Trichoderma viride e Trichoderma stromaticum - Hurmann, Eliéte Moura de Souza (2016)
Trichoderma spp. is a promising antagonist, the development and use of products based on this organism gives us the opportunity not only to reduce health risks, but also costs and environmental damage. This work aimed to analyze the efficiency of Trichoderma viride extracts and Trichoderma stromaticum against some microorganisms of interest in clinical medicine, agriculture and fish farming. Among them Colletotrichum musae, banana anthracnose causes, Saprolegnia, which affects fish eggs and some bacteria that cause harm to human health. The dichlorometane extracts were tested at various concentrations, and as positive control a commercial antimicrobial. Inhibition of the pathogen was verified directly by paired cultivation technique. The antimicrobial activity of the extracts was evaluated by disk diffusion and the determination of minimum inhibitory concentration (MIC) by microdilution test broth. In situ tests were done in the fruit inoculating the pathogenic fungus and treated with the extracts and the sensory analysis where it was determined the acceptance of the product. In cultivation paired the Trichoderma spp. inhibited the growth of pathogens being 0.05% significance level. In the disk diffusion test results were positive, and for E. coli and Aeromonas hydrophila gave the best results. MIC against microorganisms of the extracts ranged from 50% to 3,125%. Given the results presented, it is concluded that the extracts were effective in in vitro inhibition of the microorganisms as well as their application in the fruits did not alter the organoleptic characteristics.